The effects of a short exercise bout on executive functions in healthy older adults - Matteo Martini; Jamie Enoch; Arthur F. Kramer (Scientific Reports)
Abstract Regular physical activity is associated with healthier brains and improved cognition among older adults. Yet, the impact of a short bout of exercise on older adults’ cognition still is not fully clarified. The present study explored the effects of 20 min of moderate-intensity aerobic exercise (on a cycle ergometer) on cognition. Forty-eight healthy older adults were randomly assigned to an exercise or a control group and completed four cognitive tests: Affective Go/No-Go (AGN), Simple Reaction Time (SRT), Spatial Working Memory (SWM) and a Backward Counting task. Tests were administered prior to and immediately after 20 min of cycling (exercise group) or rest (control group). Mixed-design 2 × 2 ANOVAs indicated a significant interaction of Group x Session, for commission errors on the positive valence of the Affective Go/No-go task, indicating that the exercise group performed better on one aspect of this inhibition test after cycling (p = 0.004), while the control group’s performance declined after rest. A similar pattern was found for the SWM, with the exercise group showing a significantly better performance after the exercise both for total error (p = 0.027) and the strategy (p = 0.002), while no improvement was observed after rest (controls). The study suggests that inhibitory control functions and working memory may be improved by a single relatively short bout of moderate exercise. However, the null effects of exercise on the other cognitive measures indicate that the neurocognitive benefits of acute exercise for older adults may be selectively sensitive to exercise parameters and to specific aspects of cognition.